SENSITIVITAS INVESTASI STUDI KASUS PADA PENINGKATAN KAPASITAS PABRIK GULA SRAGI PT.PERKEBUNAN NUSANTARA IX - Suwandhi; Dyah Puspasari (Jurnal Bisnis Terapan, 2021)
This study aims to determine the sensitivity of the increase or decrease in the selling price of sugar and drops, then the investment value, and the cost of production to the IRR obtained from the investment decision to increase the capacity of the Sragi Sugar Factory. Hypothesis testing is carried out on the results of the calculation of investment analysis which includes several commonly used parameters, namely Net present value (NPV), Internal rate of return (IRR), Profitability Index (PI), and Payback Period (PP), in this case as a comparison used The results of the IRR calculation. The results of the sensitivity study found that the selling price has the highest sensitivity, then the second is the investment value, while the cost of goods manufactured has the lowest sensitivity. The results of tests carried out on three parameters show that there is a significant change between the Selling Price, Investment Value and Cost of Production with the calculation of the IRR of an investment.